左翼作家马宁的南洋叙事 = The Nanyang narrative of left-wing writer Ma Ning - 魏日华 Wee, Ri Hua (Nanyang Technological University, 2023)
中国左翼作家马宁，曾三次下南洋到新马地区，并且是战前新马文坛的推动者之一。在新马的期间，马宁不仅活跃于马来亚共产党的宣传工作、担任《南洋文艺》文刊的主编、还创写了以真实南洋社会为背景的几个独幕剧剧本，而其中四个剧本曾在新加坡的戏院出演，轰动了当时的南洋华侨社会。马宁的文学作品深受中国“革命文学”的影响，因此除了极具写实主义的特色外，其作品还关注下层人士的生活与苦难。马宁常以自身的经历或见闻作为创作的素材，例如他回国后抒写的散文《南洋风雨》就是记录了他几次下南洋的经历。本文将以马宁的南洋作品为个案，通过文本细读、归纳与分析的方式梳理作品中的南洋华人形象与南洋色彩，以此来了解30、40年代南洋华人的生活与社会。Chinese Left-wing writer Ma Ning travelled three times through the South Seas to the region of Singapore and Malaysia. He is one of the leading writers in the pre-war literary world of Singapore and Malaysia. During that period, Ma Ning was an active member of the Malayan Communist Party and helped in propagandistic advertising. He also served as chief editor to the Nanyang Wen Yi publication. Besides that, he wrote several one-act scripts based on the Nanyang society, in which four of them were staged in the theatre of Singapore. As a result, it caused a sensation in Chinese communities across the Nanyang region. Ma Ning’s literary works were deeply affected by the Chinese “Revolutionary Literature”. His works showed the characteristics of realism and he also paid close attention to the lives and sufferings of the lower classes. Ma Ning’s prose, the Nanyang Fengyu, recorded some of his experiences at Nanyang. Through close reading, analyzing, and summarizing Ma Ning’s Nanyang literary works, this paper seeks to explore the imagery of Chinese living in Nanyang and the “Nanyang Colors” in his works. Since most of Ma Ning’s work is set between the 1930s and1940s, this serves as a good avenue to get a clearer understanding of the life of the Chinese community during that period.